Baseline Data Report 2009-2010 : Demographic Profiles of Quebec's English-speaking Communities by selected CSSS Territories - Pocock, Joanne; Warnke, Jan (Community Health and Social Services Network (CHSSN), 2010)
This document presents selected demographic characteristics of the English-speaking population of the CSSS territories in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI) of the Community Health and Social Services Network (CHSSN). The information presented is drawn from the 2006 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec's official language minoritty community.
Keywords: Official Language Minority Community (OLMC)

[Annual Report 2009-2010] - NDG Community Council (NDGCC) (2010)

[Annual Report 2009-2010] - NDG Community Council (NDGCC) (2010)